The Role of Networking and Mastermind Groups in The Development of Female Entrepreneurship: A Qualitative and Quantitative Research in Poland - Izabela AUGUŚCIAK1; Monika ŚPIEWAK-SZYJKA2 (Communications of International Proceedings, 2025)
Female entrepreneurship is a rapidly growing area of the economy, where social capital increasingly supports business success. This study examined how networking and mastermind groups enhance business competences, agency, and professional effectiveness among female entrepreneurs, and the benefits they bring to business growth. While existing literature focuses mainly on economic and institutional factors, it overlooks the role of social relationships, mentoring, and collective learning. This study addresses that gap by analysing the practical and psychological effects of participation in entrepreneurial networks. The study was conducted using a survey of 176 female entrepreneurs, of whom 121 provided complete responses. The questionnaire included closed and semi-open questions, allowing for an assessment of the frequency and forms of participation in networking and masterminds, as well as the perceived benefits for business development. The results indicate that networking and masterminds play a key role in women's professional development, supporting knowledge exchange (76.2%), building business relationships (66.7%), personal development (57.1%) and motivation (52.4%). More than half of the respondents (52.4%) also recognise the positive impact of these activities on revenue growth. At the same time, the relatively low prevalence of participation in mastermind groups suggests a need to further popularise this form of support. The results confirm that relationships based on trust, cooperation and knowledge sharing are an important resource that strengthens women's entrepreneurship and their ability to build sustainable, scalable business models.
Keywords: women's entrepreneurship; networking; mastermind groups; social support; professional development for women